Comparison of efficacies of different treatments for nontuberculous mycobacterial pulmonary disease in Anhui Province, China - Zhaoyu Zha; Long Gao; Dongping Wang; Dongfang Xu; Yanyan Liu; Yi Liu; Shengsheng Liu; Jiabin Li; Wenhong Lin (Journal of Infection in Developing Countries)
Introduction: Although nontuberculous mycobacterial (NTM) infection is a common cause of pulmonary disease worldwide, few studies have focused on epidemiological and therapeutic factors related to NTM cases in Anhui Province, China. This retrospective study aimed to identify aetiological and clinical factors, and treatment outcomes of patients with NTM pulmonary disease (NTMPD) in Anhui.